PA and NP productivity in the Veterans Health Administration. Issue 7 (July 2016) - Moran, Eileen A.; Basa, Edesha; Gao, Jian; Woodmansee, Denni; Almenoff, Peter L.; Hooker, Roderick S.
Abstract : ABSTRACT: This study assessed the 2014 clinical productivity of 5, 959 physician assistants (PAs) and nurse practitioners (NPs) in the US Department of Veterans Affairs' Veterans Health Administration (VHA). Total work relative value units divided by the direct clinical full-time equivalent measured annual productivity, and correlated factors were examined using weighted analysis of variance. PAs and NPs in adult primary care roles were more productive than those in other specialties. Both providers were more productive in rural than in nonrural settings and less productive in teaching than nonteaching hospitals. Men were slightly more productive than women but age and years of VHA employment were not correlates of productivity. PAs were more productive when their scope of practice allowed significant autonomy; NP productivity was unaffected by supervisory requirements. PAs and NPs are an important component of the VHA provider workforce, and their productivity correlates with a number of factors. More organizational research is necessary to better understand the contributing roles PAs and NPs provide in a rapidly evolving, vertically integrated, national health delivery system.